Biomechanical properties of Bruch's membrane-choroid complex and their influence on optic nerve head biomechanics - Wang, Xiaofei; Jonas, Jost B. (Investigative ophthalmology & visual science, 2018)
Purpose: The purpose of this study was to measure the rupture pressure and the biomechanical properties of porcine Bruch's membrane (BM)-choroid complex (BMCC) and the influences of BM on optic nerve head (ONH) tissues. - Methods: The biomechanical properties of BMCC were extracted through uniaxial tensile tests of 10 BMCC specimens from 10 porcine eyes; the rupture pressures of BMCC were measured through burst tests of 20 porcine eyes; and the influence of BM on IOP-induced ONH deformations were investigated using finite element (FE) analysis. - Results: Uniaxial experimental results showed that the average elastic (tangent) moduli of BMCC samples at 0% and 5% strain were 1.60 ± 0.81 and 2.44 ± 1.02 MPa, respectively. Burst tests showed that, on average, BMCC could sustain an IOP of 82 mm Hg before rupture. FE simulation results predicted that, under elevated IOP, prelamina tissue strains increased with increasing BM stiffness. On the contrary, lamina cribrosa strains showed an opposite trend but the effects were small. - Conclusions: BMCC stiffness is comparable or higher than those of other ocular tissues and can sustain a relatively high pressure before rupture. Additionally, BM may have a nonnegligible influence on IOP-induced ONH deformations.
Gesehen am 19.06.2019